What's new in AI : audio collection 2023 - Anadiotis, George (O'Reilly Media, Inc., 2023)
This is the one stop shop for all of the What's New in AI interviews of 2023 in their audio format. Keep up-to-date with George Anadiotis and his colleagues on their AI journeys.